Impact of Mahakali River Flood on Residential Areas in Bheemdatt Municipality, Nepal (Far Western Review, 2024)
Floods are devastating natural disasters that can be caused by prolonged rainfall, cloudbursts, the combined effects of snowmelt and rainfall, glacial lake outbursts, and dam failures from landslides. The impacts of floods include loss of life and livestock, as well as extensive damage to agriculture and houses. This study aims to assess the physical impact of Mahakali River flooding on residential areas in Bheemdatt Municipality. A descriptive research design was used, with data collected from 210 students, seven school headmasters/principals, and 42 school teachers using structured questionnaires. Seven schools in flood-prone areas of Bheemdatt Municipality were selected for the study. Inundation maps were prepared by using the 1D HEC-RAS model, and data analysis was performed using simple statistical tools and Arc GIS. The study found that flooding from the Mahakali River significantly impacted residential areas, particularly those located near the river. Respondents reported severe crop damage, with many villages experiencing infrastructure damage, loss of livestock, and displacement of residents. The flooding has created both short-term and long-term challenges, including forced migration in vulnerable areas. Based on the findings; it is recommended that the Government of Nepal take immediate action to mitigate flood risks. Specific measures should include conducting flood risk assessments for flood-prone wards, implementing flood defenses, increasing public awareness, and providing emergency preparedness training for residents in high-risk areas. These actions are essential to reduce flood impacts and enhance community resilience in Bheemdatt Municipality.